2022
DOI: 10.3389/fevo.2022.839384
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Seasonality Regulates Community Evenness in Neotropical Bat Communities

Abstract: Evenness is a key community property that provides insights into resource acquisition and ecosystem functioning. However, it is unclear how other community properties influence evenness after integrating the effect of environmental gradients. Using 49 neotropical bat communities, we tested the hypothesis that evenness increases in communities that have low species richness and low biomass because the negative effect of richness and biomass on evenness is regulated by environmental seasonality. We selected amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Estrada-Villegas et al . (2022) explored factors affecting community evenness in Neotropical bat communities, and found that increasing temperature seasonality reduces species evenness, as well as biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrada-Villegas et al . (2022) explored factors affecting community evenness in Neotropical bat communities, and found that increasing temperature seasonality reduces species evenness, as well as biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Morales-Martínez et al (2018) found that high beta diversity (species turnover among sites) was associated with precipitation seasonality in Colombian Llanos communities. Estrada-Villegas et al (2022) explored factors affecting community evenness in Neotropical bat communities, and found that increasing temperature seasonality reduces species evenness, as well as biomass.…”
Section: Similarities Among Bat Communitiesmentioning
confidence: 99%